Employee relationship management in globalised context - Khurana, Karishma (International Journal of Psychosocial Rehabilitation, 2020)
All human beings are social creatures as they yearn for love, friendship and favourable interactions around them. These instincts are as natural for them as is the need for water and food. Maintaining positive relationship at work and around ourselves is crucial to foster productivity, boost morale, reducing labour turnovers and embracing changes positively without any resistance. Any relationship whether between a guru and disciple, employer and employee, superior and subordinate or principle and agent is said to be healthy if it is based on pillars of trust, mindfulness, respect, honesty, integrity, openness to diversity and communication. Positive relationship at workplace is the first step in career building and career progress. Healthy or poor relationships have an impact on our performance and achievements in life. The money and wealth that an entrepreneur can cultivate by keeping employees happy and satisfied shall promote innovation, creativity, growth of enterprise, strengthen the commerce and networking of business. Successful employee relationships in an organisation are based on the principles of psychological contract which consist of various mutual expectations that both employer and employee have towards each other. The dynamics of interpersonal relationships among employees is the most valuable tool for developing long lasting and enduring relationships and since it’s some complex phenomena, it can take months or years to blossom. It is still easy to motivate the employees using a right mix of financial and non-financial incentives, but the herculean task comes in keeping them happy. After all that is the magical secret that all the companies strive for in the long run!.